Bacterial strain type and TEM-1 enzyme allele impact antibiotic susceptibility distribution in monoclonal populations: a single-cell droplet approach - Shahab Shahryari; Shakeel Ahmad; Ilona Paulina Foik; Paweł Jankowski; Adam Samborski; Marcin Równicki; Shreyas Kandhadai Vasantham; Piotr Garstecki (Royal Society Open Science, 2025)
Bacterial populations can display different susceptibilities to antibiotics among individual cells, even though they originate from the same parent cell. This variability can lead to treatment failure and the emergence of resistant bacteria. Understanding the factors influencing this variability is crucial for developing effective antibiotic treatments. The underlying cause of variation in susceptibility distribution within bacterial populations remains unclear, necessitating the development of new tools for measurement. Here, we use a droplet microfluidic single-cell antibiotic susceptibility assay and focus on antibiotic resistance conveyed by the TEM β-lactamases family. We investigate how the catalytic activity of β-lactamase, and the genetic characteristics of the host strains affect the susceptibility distribution within bacterial populations at the single-cell level. For this purpose, we selected TEM-1 with the least catalytic activity against cefotaxime, followed by its two variants, R164S and G238S, exhibiting moderate and significant catalytic activity, respectively. The results showed that increasing the catalytic activity causes an increase in the population’s mean level of antibiotic resistance. While the type of β-lactamase influences the susceptibility distribution of the strains, this effect is independent of the catalytic activity of the strains. Besides, the genetic characteristics of the strains receiving the β-lactam resistance gene is an important factor that plays a role in the distribution of susceptibility.